Peran Dakwah dalam Meningkatkan Literasi Keuangan Syariah: Studi pada Pasar Sukuk di Indonesia - Ahmad Yudhira (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2024)
This study aims to explore the role of dawah in enhancing Sharia financial literacy and supporting the growth of the sukuk market in Indonesia. Using a literature review methodology, this research analyzes various academic and institutional sources to identify the contributions, challenges, and opportunities of dawah in Sharia financial literacy initiatives. The findings indicate that dawah significantly enhances public awareness and understanding of Sharia-compliant financial principles and products, such as sukuk, through educational programs, digital campaigns, and community outreach. However, challenges persist, including the complexity of financial products, geographical and demographic diversity, and the need for transparency in financial management. Despite these obstacles, dawah promotes sukuk as an ethical and viable investment option and fosters collaboration among religious leaders, financial institutions, and the government. In conclusion, dawah serves as a strategic tool to bridge gaps in Sharia financial literacy, facilitating broader participation in Islamic financial systems and driving the sukuk market's growth in Indonesia.